Prerequisites for developing ''green logistics'' at railway transport - Чеклов, Володимир Федорович; Чеклова, Валентина Михайлівна (Technology audit and production reserves, 2014)
The urgency of improving environmental conditions and increasing the effective use of natural resources is considered in the paper. The main objective of the research lies in determining prerequisites for developing "green" logistics at railway transport. The data analysis concerning this matter is topical for Ukraine, as ecology issue is the most urgent nowadays. However, there are a number of problems, hindering the development of "green" logistics. They include the absence of relevant legislative database, the lack of specialists in the field of "green" logistics and eco-transport, and also negative appeal for investment. The research results can be applied to railway transport, which is in a desperate need of introducing innovative technologies for improving environmental safety, quality and reliability of its running, safe railway operation. We suggest distinguishing one of the main trends of logistics development in Ukraine today, i.e. ecologization, involving implementation of measures for reducing negative impact of rail transport on the environment and setting up of effective environmental measures at other means of transport that will help to improve the ecological situation in Ukraine.